2013
DOI: 10.7860/jcdr/2013/4658.2942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcohol Withdrawl on Glutathione S-transferase, Total Antioxidant Capacity and Amylase in Blood and Saliva of Alcohol-Dependent Males

Abstract: Introduction: Alcohol biomarkers help in the early detection of alcoholism and its complications. There is a paucity of studies in India on the salivary markers of systemic diseases in general and on salivary alcohol biomarkers in particular.Objectives: The present study was aimed at assessing the effect of alcohol withdrawal on the antioxidants and amylase in blood and saliva, and at finding the correlation between the blood and the salivary parameters in alcoholics.Methods: Sixty alcohol-dependent males who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The highest sensitivity of up to 99% was observed for Peth 31, 41 that showed a rapid decrease at the beginning of withdrawal, a slow decline after the first few days, and persistence at low levels beyond 19d of abstinence 42. Apart from biomarkers detected in blood and urine samples, saliva is a promising and easy accessible material to detect glycomarkers of oxidative stress,43, 44 but the reproducibility and validity in Peth has to be proven for clinical routine application 45. As an antibody based flash test is available for detection of EtG in urine with good sensitivity and specificity, this parameter is the most promising one to be integrated in routine laboratory settings and in screening of patients at risk to develop AWS 46…”
Section: Biomarkersmentioning
confidence: 99%
“…The highest sensitivity of up to 99% was observed for Peth 31, 41 that showed a rapid decrease at the beginning of withdrawal, a slow decline after the first few days, and persistence at low levels beyond 19d of abstinence 42. Apart from biomarkers detected in blood and urine samples, saliva is a promising and easy accessible material to detect glycomarkers of oxidative stress,43, 44 but the reproducibility and validity in Peth has to be proven for clinical routine application 45. As an antibody based flash test is available for detection of EtG in urine with good sensitivity and specificity, this parameter is the most promising one to be integrated in routine laboratory settings and in screening of patients at risk to develop AWS 46…”
Section: Biomarkersmentioning
confidence: 99%
“…On the contrary, alcohol-dependent subjects showed significantly lower TAC in blood and saliva as compared to those in the controls and the alcohol withdrawal caused an increase in the TAC to near-control values [ 102 ].…”
Section: Age Gender and Lifestyle Factorsmentioning
confidence: 99%
“…Lower doses of alcohol administered in an intermittent fashion across 90 days also produced reductions in total GSH levels and increases in oxidized proteins and lipids in cortex and cerebellum [81]. Evidence has demonstrated that individuals with alcohol use disorders (AUDs) have decreased GSH activity and reduced plasma and salivary content of GST [82,83]. However, some studies have reported increased GST activity in blood of alcoholics [84,85].…”
Section: Drugs Of Abuse and Oxidative/nitrosative Stressmentioning
confidence: 99%